Vocational education and training 2020 : consequences for continuing development of the recognised-occupation model - Esser, Friedrich Hubert [Interviewer]; Bittner-Kelber, Johanna [Interviewter]; Gießler, Thomas [Interviewter]; Hartwich, Esther [Interviewter]; Scheffler, Beate [Interviewter]; Sondermann, Thomas [Interviewter]; Spöttl, Georg [Interviewter] (My University, 2013)
"The key challenges for vocational education and training (VET) are demographic change with all its consequences including the implications for securing the skilled workforce, and internationalisation in business and society and the associated task of integration. We must bear these aspects in mind for the continuing development of the VET system - that was one of the central messages at the 2011 BIBB Congress in Berlin. What are the likely repercussions for the continuing development of the model of the recognised occupation? Within the framework of communication between research, policy and practice pursued at BIBB, this question was explored in order to gather answers from the principal players in VET policy, who influence the future elaboration of recognised occupations. This yielded a range of comments that are not only interesting but also practicable, and are presented in this article." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 1.2.3.2 Anforderungen & Bedarfe; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; Berufsbildungspolitik; Fachkräftebedarf; Beruflichkeit; Durchlässigkeit im Bildungssystem; Deutscher Qualifikationsrahmen